Analisis fiqih jinayah terhadap pencabulan anak di bawah umur - Bawon, Jumrotul (Maliki Interdisciplinary Journal, 2023)
Fornication is a crime that defames honor, manners and is contrary to religion and morality. Children are the successors and ideals of the nation that must be protected by the existence of jinayah fiqh arrangements. That way children get the right to live, develop, love and also protection from acts of sexual abuse. This study aims to review the problems related to sexual abuse of minors which are currently rife so that children get welfare. This research is classified as qualitative data research, library research by collecting various literature. The results of this study explain that the crime of sexual immorality is included in the jarimah ta’zir, because the rules for this crime are not regulated in the Al-Qur’an and Hadith. In Islamic criminal law, obscenity is analogous to a crime similar to adultery and the perpetrator (muhsan) is stoned to death, while the perpetrator (ghairu muhsan) is whipped one hundred times and exiled.